2022
DOI: 10.1097/rlu.0000000000004222
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of 177Lu-PSMA Radionuclide Treatment in Advanced Prostate Cancer and Its Association With Clinical Parameters

Abstract: Purpose: This study was set out to analyze the efficacy and safety of 177 Lu-PSMA-617 (LuPSMA) treatment in metastatic castration-resistant prostate cancer (mCRPC) patients. Patients and Methods: Progressive mCRPC patients who received at least 1 cycle of LuPSMA therapy were evaluated retrospectively. Demographic, clinic, and histopathological data were documented. Treatment efficacy was determined based on biochemical response criteria (Prostate Cancer Clinical Trial Working Group 3), and toxicity rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Other two studies did not report data about PSA changes after early [177Lu] Lu-PSMA cycles while a third article included a sample <30 patients, respectively. Finally, nine studies from databases and three from citation searching were included in our present study 28,32,34,35,[42][43][44][45][46][47][48][49] for a total of 1646 patients. Characteristics of included studies are reported in Table 1.…”
Section: Search Results and Studies Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other two studies did not report data about PSA changes after early [177Lu] Lu-PSMA cycles while a third article included a sample <30 patients, respectively. Finally, nine studies from databases and three from citation searching were included in our present study 28,32,34,35,[42][43][44][45][46][47][48][49] for a total of 1646 patients. Characteristics of included studies are reported in Table 1.…”
Section: Search Results and Studies Characteristicsmentioning
confidence: 99%
“…The most recent study started in 2016 and were completed within 2020. Six studies assessed PSA changes through PCWG3 criteria 28,32,35,44,45,47 . Among six remaining studies, five assessed PSA considering any PSA decline, PSA decline ≥50% and PSA increase comparing post‐RLT to baseline PSA values, respectively 34,42,43,46,48 while one study considered any PSA change (decrease or increase) of at least 25% of the baseline value 49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…177 Lu-PSMA-617 has prolonged imaging-based progression-free survival and overall survival in mCRPC (metastatic castration-resistant prostate cancer) with a low incidence of acute adverse effects. [1][2][3][4][5] However, a complete metabolic response (PERCIST 1.0) upon imaging with disappearance of pain is uncommon. [6][7][8] This case suggests that 177 Lu-PSMA-617 treatment is an effective and reliable treatment option to relieve the pain in and delay the progression of mCRPC.…”
mentioning
confidence: 99%
“… A – D , 177 Lu-PSMA therapy is gaining momentum in achieving desirable results with minimal adverse effects in mCRPC 5–8 . The patient was referred for 4 cycles 177 Lu-PSMA therapy.…”
mentioning
confidence: 99%